Analysis of Environmentally Conscious Characters in Class XI Science Students at MA Radhiatul Adawiyah Mangga Tiga, Makassar City - Mimi Natasya; Muhammad Tang; Kamaruddin Kamaruddin; Rosika Indri Karadona (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to analyze the development of environmentally conscious character among Class XI Science students at MA Radhiatul Adawiyah Mangga Tiga, Makassar City. As environmental issues become increasingly urgent, shaping students’ awareness and responsibility towards nature is critical. This research employs a qualitative descriptive method, using observation, interviews, and documentation as data collection techniques. The findings reveal that the environmentally conscious character in students is reflected through various behaviors, such as waste segregation, participation in school greening programs, and a sense of responsibility in maintaining cleanliness. The formation of these characters is supported by the integration of environmental education into Islamic learning, school policies, teacher modeling, and student engagement in extracurricular environmental activities. The study concludes that a holistic and consistent approach within the school environment significantly contributes to nurturing students’ environmentally responsible behavior.